Work content of Norwegian occupational physicians. - Wannag, Axel; Nord, E (Scandinavian Journal of Work, Environment & Health, 1993)
There is little empirical knowledge of the work done in occupational health services. In a study of the work of 50 Norwegian occupational physicians, their work on 249 workdays was recorded and classified into nine different categories according to the work content. Most (40%) of the work concerned work environment matters, 26% went to nonwork-related activities, 18% was for administration, 4% was for personal proficiency, and 12% went to various other activities. A total of 36% of the work concerned preventive activities, and 30% involved curative activities, of which two-thirds (22%) was for nonwork-related illnesses. This latter figure seems large in comparison with the preventive aims of occupational health services given by the Norwegian labor inspectorate. The physicians spent little time on educating employees about work environment matters and on new projects to ensure good work environment standards. The amount of activity involving occupational rehabilitation was fair.